Detection methodology of chicken fat impurities in sunflower oil - Кіщенко, Володимир Анатолійович; Левчук, Ірина Володимирівна; Голубець, Ольга Валеріївна; Тимченко, Валентина Кузьмівна; Куниця, Катерина Вікторівна (Technology audit and production reserves, 2015)
The paper presents the results of a study of the possibility of using methods for determining the fatty acid, acyl glyceric and composition of sterol fraction to detect falsification of sunflower oil by chicken fat. It is analyzed the state of regulatory and scientific information on the methods of oil and fat identification and identified the need to establish regulations on melted chicken fat and its blends with sunflower oil. It is experimentally investigated the possibility of using methods for determining the fatty acid, acyl glyceric and composition of sterol fraction to detect falsification of sunflower oil by chicken fat. It is established and confirmed by the round of inter-laboratory testing of sunflower oil samples mixed with chicken fat that the main method to detect forgery is the method of determination of sterol fraction that allows detecting even the 0,5 % of sterol impurities of animal origin and additional method is the method of determining an individual acyl glyceric composition.